Effects of wind flow structure, particle flow and deposition pattern on photovoltaic energy harvest around a block. (1st November 2019) - Huang, Wenfeng; Zhou, Kun; Sun, Ke; He, Zhu
Highlights: Integrated study of wind flow vortex, particle dynamics and influences on PV efficiency. Observed horse-shoe and pair vortexes behind the block. Tracked particle trajectory and deposition conditions around block surface. Conducted particle-deposition-induced transmittance reduction analysis. Analyzed particle injection location and PV efficiency reduction for different surfaces. Abstract: The energy harvest of solar photovoltaic (PV) system is affected by many factors, among which the influence of dust deposition on photovoltaic panels is a prominent problem. This paper briefly introduced studies of dust deposition on PV panels especially by modeling and computational methods in recent years. Then, the main focus was to numerically study and analyze the influence of wind flow structure and particle deposition on PV panels combined with improved models and programs. Two-dimensional (2D) and three-dimensional (3D) cases were simulated and well compared with experimental data. 3D case results showed a shorter vortex behind the block and stronger turbulence in front of it. Tracked particle streams clearly showed the horse-shoe vortices around the block and pair vortex behind the block. Particle deposition, PV cover transmittance and efficiency reduction were larger on the windward roof and the windward wall under suspended dust environment, while leeward roof had low reduction. Under current condition, PV efficiency reduction generally increased with particle Stokes number on windward roof, while that trend on windward wall was reversed. These simulation process, findings and short view would provide a guidance to apply computational and particle tracking method on block surfaces, PV surfaces and on particle mitigation strategies.